HIV healthcare providers’ perceptions on smoking behavior among PLHIV and smoking cessation service provision in HIV clinics in Uganda - Namusisi, Kellen Nyamurungi; Frances, Thirlway; Noreen, D. Mdege; Matovu, Joseph K. B. (Tobacco Prevention & Cessation, 2021)
Integration of smoking cessation interventions into HIV care can play a crucial role in reducing the growing burden of disease due to smoking among people living with HIV (PLHIV). However, there is a dearth of information on HIV care providers’ perspectives towards integrating smoking cessation interventions into HIV care programs. We explored HIV healthcare providers’ perceptions on the smoking behavior among PLHIV, and the provision of smoking cessation services to PLHIV who smoke within HIV care services in Uganda. METHODS Semi-structured face-to-face qualitative interviews were conducted with 12 HIV care providers between October and November 2019. Data were collected on perceptions on smoking among HIV-positive patients enrolled in HIV care, support provided to PLHIV who smoke to quit and integrating smoking cessation services into HIV care programs. Data were analyzed deductively following a thematic framework approach. RESULTS Findings show that: 1) HIV care providers in HIV clinics had low knowledge on the prevalence and magnitude of smoking among PLHIV who attended the clinics; 2) HIV care providers did not routinely screen HIV-positive patients for smoking and offered sub-optimal smoking cessation services; and 3) HIV care providers had a positive attitude towards integration of tobacco smoking cessation services into HIV care programs but called for support in form of guidelines, capacity building and strengthening of data collection and use as part of the integration process. CONCLUSIONS Our study shows that HIV care providers did not routinely screen for tobacco use among PLHIV and offered suboptimal cessation support to smoking patients, but had a positive attitude towards the integration of tobacco smoking into HIV care programs. These findings suggest a favorable ground for integrating tobacco smoking cessation interventions into HIV care programs.